A common variant at the TERT-CLPTM1L locus is associated with estrogen receptorĝ€"negative breast cancer - Haiman, C.A.; Chen, G.K.; Vachon, C.M.; Canzian, F.; Dunning, A.; Millikan, R.C.; Wang, X.; Ademuyiwa, F.; Ahmed, S; Ambrosone, C.B.; Baglietto, L.; Balleine, R.; et al. (Nature Genetics, 2011)
Estrogen receptor (ER)-negative breast cancer shows a higher incidence in women of African ancestry compared to women of European ancestry. In search of common risk alleles for ER-negative breast cancer, we combined genome-wide association study (GWAS) data from women of African ancestry (1,004 ER-negative cases and 2,745 controls) and European ancestry (1,718 ER-negative cases and 3,670 controls), with replication testing conducted in an additional 2,292 ER-negative cases and 16,901 controls of European ancestry. We identified a common risk variant for ER-negative breast cancer at the TERT-CLPTM1L locus on chromosome 5p15 (rs10069690: per-allele odds ratio (OR) = 1.18 per allele, P = 1.0 × 10 -10). The variant was also significantly associated with triple-negative (ER-negative, progesterone receptor (PR)-negative and human epidermal growth factor-2 (HER2)-negative) breast cancer (OR = 1.25, P = 1.1 × 10 -9), particularly in younger women (<50 years of age) (OR = 1.48, P = 1.9 × 10 -9). Our results identify a genetic locus associated with estrogen receptor negative breast cancer subtypes in multiple populations. © 2011 Nature America, Inc. All rights reserved.